Unravelling the nexus of microfinance and women's non-communicable disease (NCD) health outcomes in Sri Lanka: An exploratory study - Gabriela Fernando; Jo Durham; Peter S. Hill; Hebe Gouda (Taylor & Francis Group, 2024)
Non-communicable diseases (NCDs) are a major contributor to the global burden of disease, increasingly impacting low-income and marginalised populations in low- and middle-income countries such as Sri Lanka. Microfinance could be a potential approach to target NCDs. Using an ethnographic approach with thematic analysis, this study explored the nexus between microfinance and NCD outcomes. In-depth interviews were conducted with 29 micro-loan borrowing women across 15 field sites within Puttalam district in Sri Lanka. The findings revealed that perceived increases in income from microfinance loans contributed to enhanced household health savings ability, enabling the purchase of medicines bought out-of-pocket and from privately owned pharmacies, and spending for NCD-relevant health emergencies and health-related transportation. Additionally, perceived income increases also influenced the behavioural risks, including the spending and consumption of food, and physical activity levels, both positively and negatively. The microfinance networks also influenced women's perceived social support, psychological stress and coping mechanisms, and health information transmission, positively and negatively. The findings from this study provide important insights on how financial inclusion programs such as microfinance influence the health determinants and outcomes relevant to NCDs. This can help address ways to target both NCDs and inequities of socioeconomically disadvantaged and marginalised populations, particularly women.